The effect of knowledge management practices on employee well-being in Malaysian Private Universities / Siti Murni Mat Khairi, Norzanah Mat Nor and Herwina Rosnan - Mat Khairi, Siti Murni; Mat Nor, Norzana; Rosnan, Herwina (UiTM Cawangan Johor, 2020)
This paper aims to propose that knowledge management (KM) practices could be a means to enhance employee well-being at work and examine how KM can develop a positive sense of employee well-being. Although employee well being is the most researched topic in the field of organisational behavior and psychology, it was rarely approached from a knowledge management perspective. Hence, this pilot study aimed to examine the effect of KM practices on employee well-being. A theoretical model concerning the connections between four KM practices (knowledge acquisition, knowledge sharing, knowledge creation and knowledge retention) and employee well-being was proposed. A survey data set of 50 responses was collected from academic staff in selected Malaysian private universities. The result was then empirically tested with structural equation modelling by using partial least squares analysis. Findings revealed that knowledge management practices were significantly linked with employee well-being. In particular, knowledge acquisition has a strong effect on employee well-being among the academic staff, followed by the knowledge retention practices. Interestingly, knowledge sharing as the key KM practice and knowledge creation seems to have the least impact on employee well-being. The key findings of this pilot study expanded the scope of the importance of KM for managers to enhance employee well-being as a priority in the organisations.